Assessment of the Effect of different Levels of Nitrogen and Plant Spacing on Growth, Yield and Quality of Onion (Allium cepa L.) cv. Agrifound Light Red - Kumari, Shilpa; Kumar, Rahul (International Journal of Bio-resource and Stress Management, 2017)
A field experiment was conducted during the year 2014−15 in order to study the effect of different levels of nitrogen and plant spacing on growth, yield and quality of onion (Allium cepa L.) cv. Agrifound Light Red. The two factor experiment was laid out in a randomized block design (RBD) with three replications. The results demonstrated that plant spacing had significant effects on growth, yield components and yield of onion. Different fertilizers combination exhibited significant variation in respect of individual bulb weight, bulb diameter and yield. The results revealed that the maximum plant height, maximum number of leaves and maximum girth thickness at 45 and 90 days after transplanting (DAT) as well as quality traits like bolting percentage, maximum bulb diameter, minimum days taken for maturity, maximum average weight of bulb and maximum total soluble solids was recorded with treatment 150 kg N ha-1. Onion cultivar Agrifound Light Red spaced at treatment(15×10 cm2) recorded the maximum plant height, number of leaves, girth thickness, bolting percentage and maximum yield per plot as well as per hactare at 45, 90 days after transplanting. While at the same treatment onion cultivar Agrifound Light Red recorded minimum days for maturity (120.56) with treatment 15×10 cm2. The results indicated that, among the sixteen treatment combinations n3m2s2 recorded maximum gross Cost : Benefit Ratio (1 : 5.67).Thus, from the present investigation it can be concluded that for optimum growth, higher yield and better quality of onion, the application of 150 kg N ha-1 and 15×10 cm2 plant spacing is very useful.